The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/polym14194087
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Microscopic Mechanism of Natural Rubber (Cis-1, 4-Polyisoprene, NR)/Polyethylene (PE) Modified Asphalt from the Perspective of Simulation

Abstract: This paper aims to study the interaction mechanism of waste tire/plastic modified asphalt from the microscopic perspective of molecules. Based on BIOVIA Materials Studio, a classic four-component asphalt model consisting of asphaltene (C149H177N3O2S2), resin (C59H85NOS), aromatic (C46H50S), and saturate (C22H46) was constructed. Waste tires are represented by natural rubber (NR), which uses cis-1, 4-polyisoprene as a repeating unit. In contrast, waste plastics are characterized by polyethylene (PE), whose opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…However, the diffusion coefficient of polar molecules is decreased by about 2% in modified asphalt systems with the addition of 5.8% PE. Yu et al [41] utilized cohesive energy density (CED) as a crucial indicator to determine the degree of polymerization (DP) of PE molecules in natural rubber-modified asphalt. However, the best DP of PE found was only 12, which poses challenges for industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the diffusion coefficient of polar molecules is decreased by about 2% in modified asphalt systems with the addition of 5.8% PE. Yu et al [41] utilized cohesive energy density (CED) as a crucial indicator to determine the degree of polymerization (DP) of PE molecules in natural rubber-modified asphalt. However, the best DP of PE found was only 12, which poses challenges for industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…MD simulations can provide insightful information on the atomic scale, making it difficult to provide experimental methods 25 . On the other hand, MD refers to the study of microscopic phenomena from a molecular or atomic point of view, so as to predict or explain macroscopic phenomena from a microscopic point of view and we can predict whether a molecule is suitable for improving a particular performance 26,27 . Li et al 28 further discussed the compatibility between an asphalt matrix and a styrene‐butadiene‐styrene (SBS) modifier using MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…25 On the other hand, MD refers to the study of microscopic phenomena from a molecular or atomic point of view, so as to predict or explain macroscopic phenomena from a microscopic point of view and we can predict whether a molecule is suitable for improving a particular performance. 26,27 Li et al 28 further discussed the compatibility between an asphalt matrix and a styrene-butadienestyrene (SBS) modifier using MD simulations. The simulation results showed that the interaction between SBS modifier and asphalt matrix improved their compatibility, and the van der Waals potential energy was dominant in the intermolecular potential energy.…”
Section: Introductionmentioning
confidence: 99%
“…Among these types, LDPE has a low density and large molecular spacing due to the areas where the saturated aromatics in the asphalt readily penetrate into the molecular chain [24]. Compared to other types of PE, LDPE can be used to significantly enhance the rheological properties of asphalt while granting it excellent high-temperature performance [25][26][27], the latter of which is important for improving the high-temperature rutting resistance of asphalt pavement [28]. Yan et al [29] showed that LDPE can enhance the high-temperature behavior of rubber-modified asphalt and improve the ability of asphalt to resist rutting.…”
Section: Introductionmentioning
confidence: 99%